2018
DOI: 10.4328/jcam.5715
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the mulligan mobilization technique in mechanical neck pain

Abstract: Aim: The aim of this study was to investigate the effectiveness of Mulligan Mobilization technique in participants with mechanical neck pain. Material and Method: A total of 40 participants (35 female, 5 male) aged between 25 to 50 years were included the study. Participants were randomly divided into two groups as Mulligan Mobilization group and control group. The participants in both groups received home exercise program. The participants were treated 10 times for two weeks. Pain (Visual Analog Scale), muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
2
11
0
1
Order By: Relevance
“…The outcomes of this trial were in line with the study by Duymaz and Yagci [16] who reported the role of MMT in the treatment of subjects with MNP. In this study, 40 subjects diagnosed with MNP were randomly allocated to two groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The outcomes of this trial were in line with the study by Duymaz and Yagci [16] who reported the role of MMT in the treatment of subjects with MNP. In this study, 40 subjects diagnosed with MNP were randomly allocated to two groups.…”
Section: Discussionsupporting
confidence: 88%
“…The outcome variables were pain measured using VAS, muscle strength using pressure biofeedback and a hand-held dynamometer, range of motion using goniometer, and functions of the neck using neck disability index. The results revealed that MMT played a definite role in refining pain, muscle strength, range of motion, and functions of the neck (16) . In a similar study, explored the efficacy of MMT concept in subjects with MNP at immediate and short-term effect after one month, Zamdanis [17] found improvement in pain and functions of the neck after nine session of treatment and after one month of follow up at MMT group.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings indicate that a number of nonpharmacological treatments improve pain and/or function for specific chronic pain conditions included in this review. This is consistent with other reviews, including recent reviews on exercise 286 acupuncture, 287 and complementary health approaches 288 for chronic pain management across various conditions, an AHRQ report on knee OA treatment, 289 and a review of chronic pain treatment guidelines on the use of manual and physical therapies. 290 The protocol for a systematic review and network meta-analysis of interventions for fibromyalgia was identified; 291 no publication timeline for this review is currently available.…”
Section: Findings In Relationship To What Is Already Knownsupporting
confidence: 82%
“…In general, serious adverse events are considered very rare for the interventions evaluated in this report and likely depend on patient factors (e.g., comorbid conditions) and provider skill and qualifications as well as characteristics of the intervention and how it is delivered. 286,[297][298][299][300][301][302] Exhaustive listing, evaluation of explicit linkage to an intervention and appraisal of evidence quality for adverse events reported in the general medical literature are beyond the scope of this review. Examples of serious adverse events reported in the medical literature for acupuncture include vascular injuries, cardiac tamponade, subarachnoid hemorrhage and infective endocarditis as described in case reports or case series.…”
Section: Limitations Of the Systematic Review Processmentioning
confidence: 99%
“…Essa disfunção é a segunda queixa musculoesquelética mais comum na população em geral e induz encargos financeiros individuais e coletivos. (DUYMAZ T, et al, 2018).…”
Section: Introductionunclassified